Systemic sclerosis impacts right heart and cardiac autonomic nervous system. Issue 3 (24th October 2017) - Tadic, Marijana; Zlatanovic, Maja; Cuspidi, Cesare; Stevanovic, Ana; Celic, Vera; Damjanov, Nemanja; Kocijancic, Vesna
Abstract: Aim: To evaluate the influence of systemic sclerosis (SSc) on right ventricular (RV) remodeling by two‐ and three‐dimensional echocardiography (2DE and 3DE) and heart rate variability (HRV). Methods: Forty‐five SSc patients and 35 age‐ and gender‐matched healthy controls underwent clinical examination, 24‐h Holter monitoring, and comprehensive 2DE and 3DE. Results: 2DE RV global and RV free wall longitudinal strains, as well as 2DE RV endocardial, mid‐myocardial, and epicardial longitudinal strains were lower in SSc subjects, who exhibited greater 3DE RV volumes but lower 3DE RV ejection fraction than controls. HRV indices were impaired in SSc subjects. These differences in RV global and free wall longitudinal strain, layer‐specific strains, and ejection fraction, were associated with HRV indices independently of demographic, clinical, and echocardiographic parameters. Modified Rodnan Skin Score, clinical indicator of skin involvement in SSc, was associated with HRV parameters, RV layer‐specific mechanics, and RV ejection fraction. Conclusion: SSc affects RV function and mechanics of all myocardial layers, as well as cardiac autonomic nervous function. HRV indices are significantly associated with RV function, RV deformation, and skin involvement in SSc patients.